2017
DOI: 10.1128/aem.02881-16
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Differential Survival of Traditional and Alternative Indicators of Fecal Pollution at Freshwater Beaches

Abstract: Alternative indicators have been developed that can be used to identify host sources of fecal pollution, yet little is known about how their distribution and fate compare to traditional indicators. Escherichia coli and enterococci were widely distributed at the six beaches studied and were detected in almost 95% of water samples (n ϭ 422) and 100% of sand samples (n ϭ 400). Berm sand contained the largest amount of E. coli (P Ͻ 0.01), whereas levels of enterococci were highest in the backshore (P Ͻ 0.01). E. c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 64 publications
2
21
0
Order By: Relevance
“…have been used to estimate fecal pollution in the past (Savichtcheva and Okabe, ). Recently, Cloutier and McLellan () reported that molecular markers from these fecal anaerobes, such as human‐associated Bacteroides and gull‐associated Catellicoccus marimammalium , accurately detected fecal pollution and correctly identified sources after a combined sewer overflow, while quantification of E. coli alone failed to indicate pollution.…”
Section: Traditional Approaches To Fecal Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…have been used to estimate fecal pollution in the past (Savichtcheva and Okabe, ). Recently, Cloutier and McLellan () reported that molecular markers from these fecal anaerobes, such as human‐associated Bacteroides and gull‐associated Catellicoccus marimammalium , accurately detected fecal pollution and correctly identified sources after a combined sewer overflow, while quantification of E. coli alone failed to indicate pollution.…”
Section: Traditional Approaches To Fecal Monitoringmentioning
confidence: 99%
“…have been used to estimate fecal pollution in the past (Savichtcheva and Okabe, 2006). Recently, Cloutier and McLellan (2017) reported that molecular markers from these fecal anaerobes, such as human-associated Bacteroides and gullassociated Catellicoccus marimammalium, accurately detected fecal pollution and correctly identified sources after a combined sewer overflow, while quantification of E. coli alone failed to indicate pollution. Despite these successes, drawbacks of fecal anaerobic indicators include geographically consistent distribution (ubiquitous presence in the feces of animal species, globally) and cross-reactivity (present in the feces of multiple animal species) (Boehm et al, 2013;Yahya et al, 2017).…”
Section: Enterococcusmentioning
confidence: 99%
“…These findings indicate that antibiotic resistance genes were acquired by multiple separate acquisition events mediated by plasmids (Villa et al, 2012;Voulgari et al, 2014). The occurrence of plasmids raises concerns about the possibility of the detected strains contributing to the dissemination of resistance genes among bacterial species in the water environment (Cloutier and McLellan, 2017;Rothenheber and Jones, 2018;Schang et al, 2016). Vancomycin-resistant enterococci were not detected in any of the water samples.…”
Section: Discussionmentioning
confidence: 99%
“…We also evaluated an internal source of fecal pollution deriving from a large colony of B. ibis residing on the mangrove island on the loko i'a interior. In order to quantify B. ibis fecal contamination, we optimized primers to C. marimammalium (GFC, Table 2), an uncharacterized Gram-positive facultative anaerobe in the order of Lactobacillales (Fusobacterium) [54] originally developed to detect fecal contamination from gulls in coastal environments [41,[55][56][57] for cattle egret fecal material ( Figure S1). Unlike Bacteroidales and Enterococcus, we found a significant decrease in egret fecal bacteria post-restoration, suggesting that increased flushing and decreased residence times had a positive impact on water quality.…”
Section: Pani Hakahaka (Close Gaps/vacancies [44]): Microbial Indicatmentioning
confidence: 99%